2013
DOI: 10.1007/s11743-013-1502-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Surface Active Properties of Novel Gemini Surfactants with Amide Groups and Rigid Spacers

Abstract: A series of novel cationic gemini surfactants, bis‐(N‐(3‐alkylamido‐propyl)‐N,N‐dimethyl)‐p‐phenylenediammonium dichloride, were synthesized. The structures of the gemini surfactants were characterized by IR, 1H NMR and 13C NMR. The Krafft temperatures of surfactants were determined through conductivity, the surface active properties in aqueous solution were studied at various temperatures by surface tension and conductivity. The thermodynamic functions of micellization process of the surfactants were also cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Ester-based gemini surfactants also show potent biological activity such as antimicrobial activity and cytotoxicity [20,21]. Research interest is also devoted to cleavable gemini surfactants bearing amide groups which are located either in the gemini spacer [23,24] or are part of hydrocarbon tails [25,26,27]. Synthesis and physicochemical investigations of novel cationic gemini surfactants with diamide spacers are reported [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Ester-based gemini surfactants also show potent biological activity such as antimicrobial activity and cytotoxicity [20,21]. Research interest is also devoted to cleavable gemini surfactants bearing amide groups which are located either in the gemini spacer [23,24] or are part of hydrocarbon tails [25,26,27]. Synthesis and physicochemical investigations of novel cationic gemini surfactants with diamide spacers are reported [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, gemini surfactants with different types of spacers have been developed with different physical and chemical properties [15][16][17]. Zhu et al [15] prepared four anionic gemini surfactants with long rigid or semi-rigid spacers, and found that all these gemini surfactants showed lower CMC and C 20 values, and that gemini surfactants with rigid spacers preferred to form vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report of sponge-like aggregates in the cationic gemini surfactant-water binary system which was probably caused by adhesion and fusion of vesicles at high surfactant concentration. Hu et al [17] synthesized a class of quaternary ammonium salt gemini surfactants with para-xylene as a rigid spacer. These gemini surfactants possessed high surface activity.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, increasing the length of hydrophobic chain, the values of CMC decreased for DHBA-m resulting from the reinforcing of the hydrophobic interaction among amphiphilic molecules. The saturated adsorption (C max ) of DHBA-m decreased, yet the area of per molecular adsorption (A min ) increased along with the length of alkyl chain from 12 to 18, which likely originates from the longer hydrophobic chain tending to curl, thus increasing the A min values [30].…”
Section: Surface Activitymentioning
confidence: 99%